Trabajo emocional: conceptos y características1Revisión de literatura (2018)
This article aims to conduct a literature review about emotional labor analyzing its main conceptualizations, research trends, and noted researchers. The review is based on exhaustive searches in journals specialized in emotional labor and organizational behavior, as well as in national books and articles. Examining the relationship between emotional labor and the results of the organization is especially necessary because one of the primary reasons why organizations require emotional labor is that emotional expression has a strong influence on sales behavior and organizational performance. Finally, the topic of emotional labor has been little explored in the field of behavioral research and organizational psychology, and c